Quantitative analysis of copper levels in areca nut plantation area - A role in increasing prevalence of oral submucous fibrosis: An in vitro study - Aurelian Jovita Alexander; Pratibha Ramani; Herald J Sherlin; S Gheena (Wolters Kluwer Medknow Publications, 2019)
Background: Oral submucous fibrosis (OSMF) commonly seen in the South Asian countries is mostly associated with the chewing of areca nut (AN). Copper content in the AN has been implicated to play a major role in the pathogenesis of OSMF. It was found that most of the AN plantations in South India commonly use a copper-based fungicide, Bordeaux mixture (BM). Objective: To evaluate the level of copper in the AN, root, and soil of the AN plantation with and without the application of BM and to correlate the role of copper in the pathogenesis of OSMF. Materials and Methods: ANs, roots, and soil were obtained from plantations located in Tanniadi, Kerala. Four areas were selected from the plantation with and without BM application. The samples were collected twice with the interval of 6 months during January 2015 and July 2015, respectively. Statistical Analysis: Arithmetic mean and standard deviation were calculated. The differences between means were calculated by paired sample t-test. Results: There was statistically significant difference in the copper content of ANs, soil, and roots from both groups (P < 0.05). Samples treated with BM showed significantly higher copper levels as compared to their counterparts in January and July 2015. Conclusions: External copper from BM and increased processing for the commercial products could collectively increase the total copper content of the commercial AN products, and this high copper concentration may be implicated to the pathogenesis and the increasing prevalence of OSMF.